THE PERCEPTION OF 10TH GRADE STUDENTS ON CHATBOT AI TO ENHANCE VOCABULARY ENRICHMENT IN WRITING POCEDURE TEXT: English - Ghaitsa Fauziyyah; Nuraini Syifa Rahayu; Muhammad Andriana Gaffar; Leny Saili Rahmah (University of Kuningan, 2025)
This study investigates the challenges of mastering technical vocabulary in writing English procedure texts in grade X high school students in Indonesia, which is caused by traditional teacher-centered teaching methods and the lack of adaptation of interactive technology. As a solution, the study proposes the integration of AI chatbots (such as ChatGPT) to provide personalized learning, instant feedback, and contextual examples. The study used a descriptive quantitative approach with a survey technique through a validated 5-point Likert scale questionnaire (Cronbach's Alpha = 0.893). Participants consisted of 57 high school students in Bandung, with data analysis using descriptive statistics. The results showed that 78.9% of students used ChatGPT to generate procedure texts, and the chatbot was rated as easy to use (mean 3.33–3.58). However, 31.6% of students stated that vocabulary was irrelevant to the curriculum, and 43.9% were not motivated to write procedure texts. The conclusion of the study confirms that AI chatbots are effective as micro-aids, but they require curriculum-based content integration, interface improvements, and collaboration with teachers to improve holistic effectiveness.